Benefits of pre-digested feed to improve growth performance and digestive health of juvenile barramundi (Lates Calcarifer) - Asni Anwar; Murni; Hamsah; Harnita Agusanty; Muhamad Ikbal; Andi Khaeriyah; Akmaluddin; Syawaluddin Soadiq; Ching Fui Fui @ Faihana Ching Abdullah; Nur Yusuf; Sitti Faridah; Imam Taukhid; et al. (Zoology Department, 2025)
A 35-day experiment was conducted to analyze the effect of feed that had been predigested using rumen microbes and Bacillus sp. on feed efficiency, protease enzyme activity in the digestive system, intestinal histology, glycogen levels, and RNA and DNA ratios, as well as growth and survival of barramundi fish (Lates calcarifer). This experiment evaluated four feeding treatments based on different biomass percentages (3, 4, 5, and 6%) under controlled rearing conditions, with each treatment designed in a triplet. All four treatments were filled with barramundi (average weight: 1.08 ± 0.01 g). The results showed that fish fed 5% and 6% biomass levels exhibited significantly higher total feed consumption, protein retention, FUE, glycogen levels, RNA/DNA ratio, daily growth rate, and absolute growth (P<0.05) compared to other treatments. This treatment also exhibited a lower FCR value compared to other treatments. The overall body chemical composition of fish shows an increase in crude protein and crude fat compared to 4–3% of fish/biomass. The average length of the villi and the highest absorption area were observed at a feeding rate of 5%. In contrast, feeding with 3% and 4% biomass resulted in reduced nutrient uptake and suboptimal growth performance. These findings suggest that the addition of predigested feed with rumen microbes and Bacillus sp., particularly at 5–6% of the biomass, significantly improves digestive efficiency and supports optimal growth in juvenile L. calcarifer. This study highlights the potential for microbial fermentation in feed to produce several advantages, improving the performance of aquaculture feed through increased nutrient availability and enzymatic support.